SAT0471 Abnormal nailfold capillaroscopic patterns are common in underweight subjects with raynaud's phenomenon. (12th June 2018) - Eman Abdulle, A.; van Roon, A.M.; Habing, M.M.; Stel, A.J.; Smit, A.J.; van Goor, H.; Mulder, D.J.
Abstract : Background: Despite the extensive research on this subject, the exact pathogenesis of RP still remains incompletely understood. The current view on this rather complex phenomena is that the imbalance between vasoconstriction and vasodilatation is purely functional and that structural vascular changes do not occur in PRP patients Although RP is a frequently occurring problem in underweight patients, microvascular changes have never been (structurally) investigated. Objectives: The aim of the current study was to investigate the relationship between microvascular abnormalities and body mass index (BMI) in subjects with Raynaud's phenomenon (RP), without an underlying connective tissue disease. Methods: Nailfold capillaroscopic patterns (NCP) were retrospectively assessed in 352 RP patients, without an underlying systemic disease (e.g. negative serology tests, and no signs of organ involvement). Patient characteristics were obtained and patients were divided by BMI category: underweight (BMI <18.5 kg/m²), normal weight (BMI 18.5–24.99 kg/m²), and overweight (BMI ≥25 kg/m²). Patterns were deemed abnormal if the mean capillary count was <20 per 3 mm, or mean number of dilated capillaries per finger was >3, or any giant capillaries were observed. Results: Approximately 70% of the underweight patients showed an abnormal NCP. This was irrespective of age and smoking behaviour. Underweight RP patients had the highest mean count of dilated capillaries (5.14 for BMI <18.5 kg/m 2 ; 4.17 BMI for 18.5–24.99 kg/m²; 2.61 for BMI ≥25 kg/m², p=0.002) and giant capillaries (1.01 for BMI <18.5 kg/m 2 ; 0.48 BMI 18.5–24.99 kg/m²; 0.23 BMI ≥25 kg/m², p=0.024). However capillary loss was not found to be significantly different (p=0.458). Furthermore, mean number of capillaries (r=0.260, p<0.001), mean number of dilated capillaries (r=−0.225, p<0.001) and mean number of giant capillaries (r=−0.221, p<0.001) were found to be associated with BMI. Conclusions: Our findings indicate NCP abnormalities are more frequently observed in underweight individuals, indicating that microvascular changes may occur independently of an underlying connective tissue disease. These findings may alert clinicians that (perivascular) adipose tissue may play a crucial role in the occurrence of Raynaud's phenomenon. Disclosure of Interest: None declared